STRATEGI MANAJEMEN KEPALA SEKOLAH DALAM MENINGKATKAN PRESTASI BELAJAR SISWADI SMA SWASTA TARUNA BANGSA SAWIT SEBERANG TAHUN PELAJARAN 2024-2025 - Elisa Dwi Ningrum; Rabukit Damanik; Maulana Akbar Sanjani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the principal's management strategies in improving student learning achievement, which include planning, organizing, implementing, and supervising all school programs. This study uses a descriptive qualitative approach, with data collection techniques through interviews, observations, and documentation conducted with the principal and teachers at the school being the object of the study. The results of the study indicate that the principal has implemented management strategies through the preparation of a systematic school work plan, proportional distribution of teacher tasks, implementation of directed teaching and learning activities, and regular supervision of program implementation. The implementation of these strategies has an impact on increasing teacher discipline, creating a conducive work climate, and improving student learning achievement. However, the implementation of management strategies still faces obstacles such as limited facilities and a lack of leadership training for principals.